The effect of pubertal status on post-activation potential in young soccer players - Estrella, R.; Ferraz, T.; Grava de Souza, J.; Oliveira Silvino, V.; Santos, M. A.; Prado, D. M. L. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Post-activation potential (PAP) is a phenomenon in which neuromuscular performance characteristics are enhanced after intense contractile stimulation. Previous studies have documented that muscle twitch force can increase through a preceding dynamic conditioning stimulus. However, there is little research regarding the effects of aerobic exercise on subsequent neuromuscular performance in young soccer players. This study examined the effect of pubertal status on PAP after maximal cardiorespiratory exercise test in young soccer players.